Lithium ion secondary battery

By using silicon carbon materials and additives with specific structures in lithium-ion batteries, the problem of volume expansion and insufficient performance of silicon materials in lithium-ion batteries is solved, and higher energy density and more stable battery performance are achieved.

CN119133573APending Publication Date: 2024-12-13ZHUHAI COSMX BATTERY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411374050.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The energy density of traditional graphite negative electrode materials is limited, which is difficult to meet the needs of high-performance lithium-ion batteries. The silicon materials have serious volume expansion problems during charging and discharging, which limits their commercial applications.

Method used

Using silicon carbon material with a specific structure as the negative electrode material, by adding ethyl 2,2-difluoroacetate and/or its derivatives and 1,1,2,2-tetrafluoroethyl-2,2, to the electrolyte solution 3,3-tetrafluoropropyl ether and/or its derivatives regulate the pore volume of siliceous carbon materials and the mass proportion of additives, improve the low-temperature and high-temperature performance of the battery, and reduce the electrolyte by forming a protective film of nitrile compounds. decomposition rate.

Benefits of technology

It effectively improves the low-temperature and high-temperature performance of lithium-ion batteries, extends the cycle life of the battery, reduces the expansion rate of silicon-carbon materials, improves structural stability and interface stability, and improves the energy density and capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133573A_ABST
    Figure CN119133573A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a lithium ion secondary battery. In the lithium ion secondary battery, a negative plate comprises a silicon carbon material; the silicon-carbon material comprises a porous carbon substrate and a silicon material distributed in pores of the porous carbon substrate; the open pore volume of the silicon carbon material is recorded as V cm < 3 > / g; the electrolyte comprises a first additive and a second additive, the first additive comprises ethyl 2, 2-difluoroacetate and / or a derivative thereof, and the second additive comprises 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether and / or a derivative thereof; the mass ratios of the first additive and the second additive are respectively recorded as A1% and A2%; a1 and A2 satisfy 5 < = A1 + A2 < = 30; and V is more than or equal to 0.0001 and less than or equal to 0.1, so that the low-temperature performance of the battery can be effectively improved, the high-temperature performance of the battery is considered, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] With the rapid development of new energy industries such as portable electronic devices and electric vehicles, the demand for high-performance lithium-ion batteries is growing, and higher requirements are placed on the energy density of lithium-ion batteries. Traditional graphite negative electrode materials are difficult to meet the needs of these high-performance applications due to their limited energy density. Silicon materials have attracted much attention due to their extremely high theoretical capacity (up to 4200mAh / g) and are considered to be one of the key materials for improving the energy density of lithium-ion batteries. However, silicon-based materials have serious volume expansion problems during the charging and discharging process, which limits their commercial application. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a lithium ion secondary battery, wherein the battery adopts a silicon-carbon material of a specific structure in the negative electrode. By adding a first additive including ethyl 2,2-difluoroacetate and / or its derivatives and a second additive including 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and / or its derivatives to the electrolyte, when the mass proportion of the first additive and the mass proportion of the second additive satisfy a specific relationship and the open pore volume of the silicon-carbon material is regulated within a suitable range, the low temperature performance of the battery can be effectively improved, the high temperature performance of the battery can be taken into account, and the cycle performance of the battery can be improved.

[0004] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0005] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon-based material and a silicon-based material; the silicon-based material includes a silicon-carbon material; the silicon-carbon material includes a core and a carbon coating layer coated on the core, and the core includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate; the open pore volume of the silicon-carbon material is recorded as Vcm 3 / g;

[0006] The electrolyte includes a first additive, wherein the first additive includes ethyl 2,2-difluoroacetate and / or its derivatives; based on the total mass of the electrolyte, the mass proportion of the first additive is denoted as A1%;

[0007] The electrolyte includes a second additive, wherein the second additive includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and / or its derivatives; based on the total mass of the electrolyte, the mass proportion of the second additive is recorded as A2%;

[0008] A1 and A2 satisfy: 5≤A1+A2≤30;

[0009] V satisfies: 0.0001≤V≤0.1.

[0010] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0011] (1) The lithium-ion secondary battery provided by the present invention can effectively improve the low-temperature performance of the battery, take into account the high-temperature performance of the battery, and improve the cycle performance of the battery by adjusting the mass ratio of the first additive and the second additive, and adjusting the open pore volume of the silicon-carbon material.

[0012] (2) The lithium-ion secondary battery provided by the present invention further adds nitrile compounds to the electrolyte, and the nitrile compounds form a protective film on the surface of the positive electrode material, which effectively prevents the direct contact between the electrolyte and the positive electrode material, reduces the decomposition rate of the electrolyte at high temperature, and can improve the high-temperature performance of the lithium-ion battery, so as to take into account both low-temperature performance and high-temperature performance.

[0013] (3) The lithium-ion secondary battery provided by the present invention can reduce the volume change of the silicon-carbon material by further adjusting the Dv50 of the silicon-carbon composite material, so that the stress of the silicon-carbon material is more uniform, and the expansion rate is reduced, thereby effectively reducing local stress concentration, reducing the risk of particle breakage and pulverization, enhancing the structural stability of the silicon-carbon material, and improving the cycle performance of the battery.

[0014] (4) The lithium-ion secondary battery provided by the present invention, by further adjusting the Dv50 of the positive electrode active material, is beneficial to increase the contact area between the positive electrode active material and the electrolyte in the electrode sheet, thereby improving the capacity and energy density of the battery; it is also beneficial to the coordination of the cyanide group in the nitrile compound with the positive electrode metal element, reducing the dissolution of the metal element, and improving the interface stability of the positive electrode sheet.

[0015] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown is a cross-sectional schematic diagram of the silicon-carbon material in an embodiment of the present invention.

[0017] Figure numerals: 1. open pore; 2. closed pore; 3. carbon coating layer; 4. porous carbon substrate; 5. silicon material. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0020] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0021] In the present invention, the term "open pore volume" refers to the volume of pores in the internal pore structure of the silicon-carbon material that are connected to the outside world, and the "open pore volume" does not include the volume of closed pores.

[0022] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0023] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon-based material and a silicon-based material; the silicon-based material includes a silicon-carbon material; the silicon-carbon material includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate; the open pore volume of the silicon-carbon material is recorded as V cm 3 / g;

[0024] The electrolyte includes a first additive, wherein the first additive includes ethyl 2,2-difluoroacetate and / or its derivatives; based on the total mass of the electrolyte, the mass proportion of the first additive is denoted as A1%;

[0025] The electrolyte includes a second additive, wherein the second additive includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and / or its derivatives; based on the total mass of the electrolyte, the mass proportion of the second additive is recorded as A2%;

[0026] A1 and A2 satisfy: 5≤A1+A2≤30;

[0027] Exemplarily, the value of A1+A2 may be 5, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30 or any point value in the range consisting of any two of the above point values.

[0028] V satisfies: 0.0001≤V≤0.1.

[0029] For example, the open pore volume V of the silicon-carbon material may be 0.0001 cm 3 / g, 0.0002cm 3 / g, 0.0004cm 3 / g, 0.0008cm 3 / g, 0.001cm 3 / g, 0.004cm 3 / g, 0.008cm 3 / g, 0.01cm 3 / g, 0.02cm 3 / g, 0.03cm 3 / g, 0.04cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.09cm 3 / g, 0.1cm 3 / g or any point value in the range consisting of the above two point values.

[0030] In the present invention, the silicon material in the pores of the porous carbon substrate mainly refers to silicon alone.

[0031] During the charge and discharge process of silicon-carbon materials, silicon materials will undergo significant volume changes, which may cause the carbon layer coated on the surface of the porous carbon base material to rupture. The structural destruction of the carbon layer will lead to the pulverization and shedding of the silicon material and the destruction of the electrode. Then, the SEI film may continue to grow and reconstruct, leading to the consumption of lithium ions, the decomposition of the electrolyte and the deposition of lithium, which will seriously affect the cycle stability and service life of the battery.

[0032] In the negative electrode of the present invention, a silicon-carbon material with a specific structure is used. The silicon-carbon material has a suitable open pore volume, which can alleviate the volume change of the silicon material during the charge and discharge process, reduce the phenomenon of material pulverization and peeling, and thus extend the cycle life of the battery; at the same time, the larger the open pore volume (V), the more conducive it is to the penetration and infiltration of the electrolyte into the silicon-carbon material, and the formation of a stable interface film, thereby improving the transmission efficiency of lithium ions and improving the capacity retention rate of the battery; but if the open pore volume (V) is too large, the tap density and volume energy density of the silicon-carbon material will be reduced.

[0033] Although adjusting the open pore volume of silicon-carbon materials is helpful to reduce the problems of poor cycle performance and low lithium ion transmission efficiency caused by large expansion of silicon materials. However, under low temperature conditions, the viscosity of the electrolyte increases and the ionic conductivity decreases, resulting in a decrease in the migration rate of lithium ions in the electrolyte, an increase in the internal resistance of the battery, and an aggravation of the battery polarization, resulting in poor low-temperature performance of batteries containing silicon-carbon negative electrodes. The present invention adds a first additive of ethyl 2,2-difluoroacetate (DFEA) and / or its derivatives, and a second additive of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (abbreviated as D2 / TTE) and / or its derivatives to the electrolyte. The fluorine atoms in DFEA can effectively weaken Li + The interaction with the solvent promotes the desolvation process at low temperatures. This desolvation effect makes it easier for lithium ions to escape from the solvation environment, thereby accelerating the migration speed of lithium ions, improving the charge and discharge efficiency of the battery at low temperatures, and helping to improve the cycle performance of the battery under low temperature conditions; and DFEA and / or its derivatives have lower binding energy, which can reduce the viscosity and melting point of the electrolyte, increase the activity and diffusion coefficient of lithium ions, and enable the battery to maintain a higher discharge efficiency at lower temperatures, thereby improving low-temperature performance. The fluorine atoms in the molecular structure of TTE and / or its derivatives replace hydrogen atoms, enhancing the stability and chemical inertness of the molecule, and can form a solvation structure containing anions, showing a lower desolvation energy barrier. When used in conjunction with DFEA and / or its derivatives, it can better improve the migration speed of lithium ions in the electrolyte under low temperature conditions, and further improve the low-temperature performance of batteries containing silicon-carbon negative electrodes.

[0034] The present invention adjusts A1 and A2 to meet 5≤A1+A2≤30, and when V meets 0.0001≤V≤0.1, the larger the open pore volume (V), the more electrolyte penetration space can be provided, which is helpful for the electrolyte to fully contact with the negative electrode material, improve the transmission efficiency of lithium ions, and reduce polarization. At the same time, the content of the first additive and the second additive A1+A2 is adjusted to increase accordingly, so that the silicon-carbon material is used in conjunction with the first additive and the second additive in the electrolyte, inhibiting the expansion of the silicon material, extending the battery cycle life, and improving the low-temperature performance of the battery. When A1+A2<5, the improvement of the low-temperature performance of the battery is not obvious; when A1+A2>30, the viscosity of the electrolyte increases, the impedance increases, and it is not conducive to the rapid charging and discharging and power output of the battery. When A1 and A2 meet 5≤A1+A2≤30, the activity and diffusion coefficient of lithium ions can be further improved, so that the battery can maintain a higher discharge efficiency at a lower temperature, and the performance of the battery under low temperature conditions is improved.

[0035] In the present invention, the open pore volume (V) of the silicon-carbon material is preferably in the range of 0.01≤V≤0.1, which is conducive to the penetration and infiltration of the electrolyte into the silicon-carbon material, forming a more stable interface film, further improving the transmission efficiency of lithium ions, and maintaining a high capacity retention rate of the battery. In addition, the synergistic effect with the first additive and the second additive in the electrolyte is better, further improving the cycle stability of the silicon-carbon material. If the open pore volume of the silicon-carbon material is too large (>0.1cm 3 / g), the porous carbon substrate is prone to collapse or deformation during the insertion and deinsertion of lithium ions, thus affecting the cycle stability and life of the battery.

[0036] In addition, DFEA and / or its derivatives, while having a lower binding energy, are beneficial to the formation of positive and negative electrodes, improve the stability of the positive and negative electrode interfaces, keep the electrolyte at a high salt dissociation degree and ion conductivity, are beneficial to the transmission kinetics of lithium ions, and help improve the charge and discharge efficiency and cycle stability of the battery, but the improvement of the high temperature performance of the battery is limited. The fluorine atoms in the molecular structure of TTE and / or its derivatives replace hydrogen atoms, enhance the stability and chemical inertness of the molecules, have higher thermal stability and chemical stability, and are beneficial to the formation of positive electrode films, which can improve the performance of the battery in high temperature and high pressure environments to a certain extent, and also reduce the gas production caused by side reactions, which is beneficial to high temperature storage. Therefore, adding a first additive including DFEA and / or its derivatives to the electrolyte, and adding a second additive including TTE and / or its derivatives, can make the battery have better low temperature performance while also taking into account high temperature performance to a certain extent.

[0037] For example, the open pore volume of the silicon-carbon material can be measured by a low-temperature nitrogen adsorption method, a true density / open and closed porosity tester, or a specific surface area analyzer.

[0038] Exemplarily, in the first additive, the chemical formula of ethyl 2,2-difluoroacetate is:

[0039]

[0040] In some embodiments, the derivative of ethyl 2,2-difluoroacetate, including but not limited to, functionalization can be performed on the ester group, or different substituent groups can be introduced into other parts of the molecule, such as substituents F, cyano (-CN), etc. The derivative of ethyl 2,2-difluoroacetate can be, for example, one of 2,2-difluoroethyl acetate, ethyl 2,2,2-trifluoroacetate, and n-butyl difluoroacetate.

[0041] Exemplarily, in the second additive, the chemical formula of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is:

[0042]

[0043] In some embodiments, the derivatives of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether include but are not limited to those obtained by introducing different functional groups, such as F, amino, carboxyl, etc., into tetrafluoroethyl or tetrafluoropropyl groups. The derivatives of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether include, for example, 1,1,2,3,3,3-pentafluoropropyl-2,2,2-trifluoroethyl ether.

[0044] In some embodiments, the first additive is ethyl 2,2-difluoroacetate; and / or the second additive is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, preferably the first additive is ethyl 2,2-difluoroacetate and the second additive is a combination of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. Further selecting ethyl 2,2-difluoroacetate and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether for use in combination can provide the battery with better low temperature performance, reduce the expansion rate of silicon-carbon materials, extend the battery cycle life, and take into account high temperature performance and improve storage gas production.

[0045] In some embodiments, the mass proportion A1 of the first additive satisfies: 1≤A1≤20, and the mass proportion A1 of the first additive can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 19%, 20%, or any point value in the range consisting of any two of the above point values, preferably 5≤A1≤15. The mass proportion A1 of the first additive further satisfies the above range, which can further promote the desolvation process at low temperature, maintain a high salt dissociation degree and ion conductivity, enable the battery to maintain a higher charge and discharge efficiency at a lower temperature, and further improve the low temperature performance and cycle stability of the battery.

[0046] In some embodiments, the mass proportion A2 of the second additive satisfies: 1≤A2≤20, and the mass proportion A2 of the second additive can be, for example, 1%, 2%, 3%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 19%, 20%, or any point value in the range consisting of any two of the above point values, preferably 2≤A2≤10. The mass proportion A2 of the second additive further satisfies the above range, which can reduce the increase in electrolyte viscosity and avoid excessive impedance, and while further improving the low temperature performance of the battery, the battery can maintain good electrochemical performance in high temperature and high pressure environments to the greatest extent.

[0047] In some embodiments, the mass proportion of silicon in the negative electrode active material is 5%-50%, and the mass proportion of silicon can be, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any point value in the range of the above two points. When the mass proportion of silicon further meets the above range, the cycle stability and service life of the battery are further improved, and when the mass proportion of silicon is too large (>50%), there is more silicon material, resulting in a large volume change in the negative electrode, causing the negative electrode to pulverize, fall off and damage the electrode, resulting in the continuous consumption of lithium ions caused by the destruction and reconstruction of the SEI film, the decomposition of the electrolyte and the deposition of lithium, which deteriorates the cycle performance of the battery.

[0048] For example, the test method for the mass percentage of silicon in the negative electrode active material can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions are: sample weight 5 mg, air as atmosphere, heating rate 10°C / min from room temperature to 900°C and constant temperature for 40 minutes. The relationship between the mass percentage of silicon-carbon material (x) and the final weight residual percentage (y) of the entire test is: x=7y / 15.

[0049] In some embodiments, the electrolyte further includes a nitrile compound; the mass proportion of the nitrile compound is recorded as N% based on the total mass of the electrolyte; A1 and N satisfy: 12≤A1+N≤25, and illustratively, the value of A1+N can be, for example, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or any point value in the range of the above two point values. A1+N satisfies the above range, and a nitrile compound is added to the electrolyte. The nitrile compound forms a protective film on the surface of the positive electrode material, which effectively prevents the direct contact between the electrolyte and the positive electrode material, reduces the decomposition rate of the electrolyte at high temperature, and can improve the high temperature performance of the lithium-ion battery, so that both low temperature performance and high temperature performance are taken into account.

[0050] In some embodiments, the mass proportion N of the nitrile compound satisfies: 2≤N≤10, and the mass proportion of the nitrile compound can be, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range of the above two point values, preferably 3≤N≤8. When the mass proportion of the nitrile compound satisfies the above range, it is avoided that the mass proportion of the nitrile compound is too large (N>10) to form an overly thick protective film on the surface of the positive electrode material to increase the resistance of the electrode, hinder the transmission of lithium ions, and cause the battery's charge and discharge performance to decrease; and it is avoided that the mass proportion of the nitrile compound is too small (N<2) to form a complete and effective protective film on the surface of the positive electrode material, resulting in increased direct contact between the electrolyte and the positive electrode material, accelerating the decomposition of the electrolyte and the corrosion of the positive electrode material.

[0051] In some embodiments, the nitrile compound includes one or more of a mononitrile compound, a dinitrile compound, and a trinitrile compound.

[0052] Illustratively, the mononitrile additive includes, but is not limited to, one or more of benzonitrile, p-toluenenitrile, and 3,5-difluorobenzonitrile.

[0053] Exemplarily, the dinitrile additive includes, but is not limited to, one or more of adiponitrile (AND), succinonitrile (SN), glutaronitrile, suberonitrile, and ethylene glycol bis(propionitrile) ether.

[0054] Illustratively, the trinitrile additive includes, but is not limited to, one or more of 1,3,6-hexanetrinitrile (HTCN), 1,2,6-hexanetrinitrile, and 1,2,3-tris(2-cyanoethoxy)propane.

[0055] In order to further reduce the viscosity of the electrolyte and improve the battery performance, the present invention further proposes: the Dv50 of the silicon-carbon material is recorded as d1μm, d1 and A1 satisfy: 1≤A1 / d1≤3; illustratively, the value of A1 / d1 can be, for example, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3 or any point value in the range of the above two point values. When d1 and A1 satisfy 1≤A1 / d1≤3, the particle size of the silicon-carbon material can provide a suitable specific surface area, increase the electrolyte infiltration contact area, increase the number of reactive active sites, and facilitate the formation of a more stable solid electrolyte interface (SEI) by DFEA and / or its derivatives in the first additive, reduce the interfacial impedance during battery charging and discharging, and inhibit lithium plating at the negative electrode, thereby further improving the low-temperature cycle stability of the battery.

[0056] In some embodiments, the Dv50 (d1) of the silicon-carbon material satisfies: 6≤d1≤12, and the Dv50 of the silicon-carbon material can be, for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, or any point value in the range of the above two point values. When the Dv50 of the silicon-carbon material further satisfies the above range, it can be avoided that when d1<6, the particle size of the silicon-carbon material is too small, the mechanical stress of the silicon material increases, which is not conducive to the structural stability of the silicon-carbon material, causing SEI film damage, aggravated side reactions, repeated growth and thickening of SEI, impedance degradation, and rapid consumption of electrolyte deteriorating the cycle life of the battery; it can also be avoided that when d1>12, the silicon-carbon material produces a more drastic volume change during the charge and discharge process, resulting in stress concentration inside the silicon-carbon material and between the silicon material and the carbon substrate, resulting in the breakage and pulverization of the silicon-carbon material.

[0057] In order to further improve the capacity and energy density of the battery and reduce the dissolution of metal elements, the present invention further proposes that: the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes a transition metal lithium oxide, and the molecular formula of the transition metal lithium oxide is Li x Co y M 1-y O2, wherein 0≤x≤1, 0≤y≤1, M includes one or more of Ni, Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr; the Dv50 of the positive electrode active material is recorded as d2μm, d2 satisfies: 10≤d2≤30, and the Dv50 of the positive electrode active material can be, for example, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm or any point value in the range composed of the above two point values. When the Dv50 of the positive electrode active material further satisfies the above range, it can increase the contact area between the active material and the electrolyte, provide more active sites, and increase the amount of lithium ion embedding, thereby improving the capacity and energy density of the battery. In addition, it can also facilitate the coordination of the cyanide group of the nitrile compounds in the electrolyte with the metal elements in the positive electrode active material, reduce the dissolution of the metal elements and prevent the destruction of the interface stability of the electrode; avoid the situation when d2>30, the capacity and energy density of the battery are not significantly improved, and avoid the situation when d2<10, the particle size of the positive electrode active material is too small, the surface energy of the positive electrode active material increases, it is easy to agglomerate and react with the electrolyte, increase the internal resistance of the battery, and reduce the cycle performance.

[0058] In the present invention, in the Dv50 of the silicon-carbon material and the Dv50 of the positive electrode active material, "Dv50" refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of the silicon-carbon material or the positive electrode active material sample reaches 50%.

[0059] Dv50 can be measured by laser particle size test method, for example, using a Malvern particle size tester, and the test steps are as follows: disperse the sample material in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02-0.03wt%) to form a mixture, ultrasonicate the mixture for 2 minutes, and then place it in a Malvern particle size tester for testing.

[0060] In some embodiments, Figure 1 As shown, the silicon-carbon material includes a core and a carbon coating layer 3 coated on the core, the core includes a porous carbon substrate 4 and a silicon material 5 distributed in the pores of the porous carbon substrate 4, wherein the closed pores 2 are closed pore structures in the core of the silicon-carbon material and are not connected to the outside world; the open pores 1 are connected to the outside world, and the open pore volume refers to the volume of the open pores 4 in the internal pore structure of the silicon-carbon material that are connected to the outside world, excluding the volume of the closed pores 2.

[0061] In some embodiments, the silicon-carbon material includes a carbon coating layer, which is coated on the surface of the porous carbon substrate and the silicon material; the thickness of the carbon coating layer is 10nm-500nm, and the thickness of the carbon coating layer can be, for example, 10nm, 20nm, 30nm, 40nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 460nm, 470nm, 480nm, 490nm, 500nm or any point value in the range composed of the above two point values. When the thickness of the carbon coating layer further meets the above range, it can further inhibit the decomposition of the electrolyte on the surface of the silicon negative electrode, which is conducive to forming a stable interface film, reducing the consumption of the electrolyte, and improving the cycle stability of the battery. The carbon coating thickness can be obtained by transmission electron microscopy (TEM) testing.

[0062] In some embodiments, the carbon-based material includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, hard carbon, and soft carbon.

[0063] In some embodiments, in the negative electrode active material, the mass proportion of carbon-based materials is 25%-98%, and the mass proportion of silicon-carbon materials is 2%-75%.

[0064] In some embodiments, the electrolyte further includes a third additive, and the third additive includes one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), tetravinylsilane (TVS), tris(trimethylsilyl) borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), and triphenyl phosphite (TPPi). Based on the total mass of the electrolyte, the mass proportion of the third additive is 8%-20%, for example, it can be 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of the above two point values. Adding the third additive to the electrolyte is conducive to forming a dense interface film, reducing side reactions, and improving the cycle life of the battery.

[0065] In some embodiments, the electrolyte includes an organic solvent, and the organic solvent includes a carbonate solvent and / or a carboxylate solvent.

[0066] Illustratively, the carbonate solvent includes, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0067] Illustratively, the carboxylate solvent includes, but is not limited to, one or more of ethyl acetate (EA), propyl acetate, n-butyl acetate, isobutyl acetate, methyl propionate (MP), propyl propionate (PP), ethyl propionate (EP), methyl butyrate, and ethyl butyrate.

[0068] In some embodiments, the electrolyte includes a lithium salt, and the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium bis(fluorosulfonyl imide) (LiFSI), 4,5-dicyano-2-trifluoromethylimidazolium lithium (LiDTI), lithium difluorophosphate (LiPO2F2) and lithium difluorobis(oxalate phosphate). Based on the total mass of the electrolyte, the mass proportion of the lithium salt is 12.5%-25%, for example, it can be 12.5%, 15%, 18%, 20%, 22%, 24%, 25% or any point value in the range composed of the above two point values. Adding a lithium salt that meets the above range to the electrolyte can improve the ionic conductivity of the electrolyte, improve the charge and discharge efficiency of the battery, and improve the fast charging performance of the battery.

[0069] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode active material layer disposed on at least one side of the current collector, the positive electrode active material layer includes a positive electrode conductive agent, and the mass proportion of the positive electrode conductive agent is 0.1%-10% based on the total mass of the positive electrode active material layer. The mass proportion of the positive electrode conductive agent can be, for example, 0.1%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range composed of two points above, preferably 0.2%-5%. When a positive electrode conductive agent is further added to the positive electrode sheet and meets the above range, the conductivity of the battery can be further improved.

[0070] In the present invention, the positive electrode conductive agent in the positive electrode sheet is not specifically limited. For example, conventional conductive agents in the art can be selected, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene.

[0071] In some embodiments, the positive electrode sheet further includes a positive electrode binder, and the mass proportion of the positive electrode binder is 0.1%-10% based on the total mass of the positive electrode active material layer. The mass proportion of the positive electrode binder can be, for example, 0.1%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range of two points above, preferably 0.2%-5%. When the positive electrode binder is further added to the positive electrode sheet and meets the above range, the mechanical strength of the positive electrode sheet can be further improved to prevent the positive electrode material from peeling or breaking during the charge and discharge process.

[0072] In the present invention, the positive electrode current collector is not particularly limited, and for example, a conventional current collector in the art may be used.

[0073] In the present invention, the positive electrode binder in the positive electrode sheet is not specifically limited. For example, conventional binders in the art may be selected, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.

[0074] In some embodiments, the negative electrode sheet includes a current collector and a negative electrode active material layer disposed on at least one side of the current collector, the negative electrode active material layer includes a negative electrode conductive agent, and / or a negative electrode binder, and the mass proportion of the negative electrode conductive agent is 0.1%-10% based on the total mass of the negative electrode active material layer. The mass proportion of the negative electrode conductive agent can be, for example, 0.1%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%. , 10% or any point value in the range consisting of any two of the above points, preferably 0.2%-5%; based on the total mass of the negative electrode active material layer, the mass proportion of the negative electrode binder is 0.1%-10%, and the mass proportion of the negative electrode binder can be, for example, 0.1%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range consisting of any two of the above points, preferably 0.2%-5%.

[0075] In some embodiments, the negative electrode active material layer of the negative electrode sheet also includes a thickener. Based on the total mass of the negative electrode active material layer, the mass proportion of the thickener is 0.1%-10%. The mass proportion of the thickener can be, for example, 0.1%, 0.3%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range composed of any two of the above point values, preferably 0.2%-5%.

[0076] In the present invention, the type of the negative electrode current collector is not specifically limited. For example, a conventional negative electrode current collector in the art, such as copper foil, may be used.

[0077] In the present invention, the types of negative electrode conductive agent and negative electrode binder are not specifically limited, and conventional conductive agent and binder types in the art can be selected.

[0078] In the present invention, the type of thickener is not specifically limited, and conventional thickeners in the art may be used, such as sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, and polytetrafluoroethylene.

[0079] In the present invention, the type of the diaphragm is not specifically limited. For example, conventional lithium-ion battery diaphragms in the art can be selected, including but not limited to woven membranes, non-woven membranes (non-woven fabrics), microporous membranes, composite membranes, diaphragm paper, rolled membranes, polyethylene microporous membranes, polypropylene microporous membranes, etc.

[0080] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0082] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0083] Example 1-1

[0084] 1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, the conductive agent carbon black, and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 97.5:1.5:1, and are fully stirred to form a uniform positive electrode slurry. The positive electrode slurry is coated on an aluminum foil, dried, rolled, and cut to obtain a positive electrode sheet.

[0085] 2) Preparation of negative electrode sheet: Weigh silicon-carbon composite material (carbon coating layer thickness is 320 nm), graphite, conductive agent carbon black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose, and disperse them in deionized water at a mass ratio of 24:73.1:0.5:1.1:1.3, stir them thoroughly to form a uniform negative electrode slurry, coat the negative electrode slurry on the negative electrode current collector copper foil, and then dry, roll and cut to obtain a negative electrode sheet.

[0086] 3) Preparation of electrolyte: In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC, PC, PP, DEFA, and TTE were mixed in a mass ratio of 10:15:35:12:8 to obtain an electrolyte solvent, and then 14.5% of lithium hexafluorophosphate (LiPF6) based on the total mass of the electrolyte was added to the electrolyte solvent. After dissolution, 5.5% of a nitrile compound additive based on the total mass of the electrolyte was added and stirred evenly. After passing the moisture and free acid tests, the electrolyte was obtained.

[0087] 4) Diaphragm: PE porous polymer film is used as the isolation membrane.

[0088] 5) Assembly of lithium-ion batteries: The positive electrode sheet, negative electrode sheet and separator prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, and the core is placed in an aluminum-plastic film packaging bag, and then a lithium-ion battery is prepared through processes such as liquid injection, formation, secondary sealing, and sorting.

[0089] 6) Battery performance test

[0090] i) Low temperature cycle performance test

[0091] The battery is discharged to 3V at a constant current of 0.2C, and after standing for 5 minutes, the lithium-ion battery is placed in a 0℃ environment. After standing for 4 hours, it is charged to the upper limit voltage (4.5V) at a constant current of 0.3C, and stands for 5 minutes and the thickness is measured as H0; then it is discharged to 3V at a constant current of 0.5C, and stands for 5 minutes. This is a charge and discharge cycle, and the charge and discharge cycle is 100 times. The highest discharge capacity of the first three cycles is recorded as the initial capacity Q0, the discharge capacity of the 100th time is Q1, and the thickness after the battery is fully charged is H1. Calculate the battery capacity retention rate = Q1 / Q0×100%; thickness change rate = H1 / H0×100%;

[0092] ii) High temperature cycle performance test

[0093] Place the lithium-ion battery in a 45°C environment, let it stand for 2 hours, then when the battery temperature is 45±2°C, charge it at a constant current of 0.7C to the upper limit voltage (4.5V), then charge it at a constant voltage of 4.5V to 0.05C, let it stand for 5 minutes and measure the thickness as H2; then discharge it at a constant current of 0.5C to 3.0V, let it stand for 5 minutes, this is a charge and discharge cycle, and the charge and discharge cycle is 500 times. The highest discharge capacity of the first three cycles is recorded as the initial capacity Q2, the discharge capacity of the 500th cycle is Q3, and the thickness after the battery is fully charged is H3. Calculate the battery capacity retention rate = Q3 / Q2×100%; thickness change rate = H3 / H2×100%;

[0094] iii) High temperature storage performance test

[0095] The fully charged battery was left to stand for 2 hours to measure the voltage, and the initial capacity was recorded as Q4. It was then stored in a 60°C high-temperature oven for 35 days, and the thickness, voltage and internal resistance were tested every 7 days. After storage, the residual capacity was tested at 0.5C discharge and recorded as Q5. The residual capacity retention rate of the battery was calculated as Q5 / Q4.

[0096] Table 1

[0097] The Example 1-3 group and the Comparative Example 1-3 are carried out with reference to the Example 1-1, and the main differences are shown in Table 1. Among them, the Example 1 group changes the open pore volume of the silicon-carbon material. The Example 2 group changes the mass proportion of the first additive. The Example 3 group changes the mass proportion of the second additive. The second additive is not added to the electrolyte of the Comparative Example 1. The first additive is not added to the Comparative Example 2. The open pore volume of the Comparative Example 3 is too large.

[0098] Table 1

[0099]

[0100] Note: “ / ” indicates that the corresponding parameter is not tested.

[0101] It can be seen from Table 1 that the present invention can effectively improve the low-temperature performance of the battery, take into account the high-temperature performance of the battery, and improve the cycle performance of the battery by adjusting the open pore volume of the silicon-carbon material and the mass ratio of the first additive and the second additive in the electrolyte.

[0102] The fourth embodiment was carried out in accordance with the first embodiment, and the main differences are shown in Table 2. In the fourth embodiment, a derivative of the first additive or a derivative of the second additive was added to the electrolyte.

[0103] Table 2

[0104]

[0105] It can be seen from Table 2 that the use of the derivative of the first additive or the derivative of the second additive can also improve the low-temperature performance of the battery, the high-temperature performance of the battery and the cycle performance of the battery.

[0106] Example 5 was carried out with reference to Example 1-1, with the main differences shown in Table 3. In Example 5, the mass proportion of the nitrile compound was changed.

[0107] Table 3

[0108]

[0109] Note: “ / ” indicates that the corresponding parameter is not tested.

[0110] It can be seen from Table 3 that the present invention can make the battery have better low-temperature performance and better high-temperature performance by adjusting the mass proportion of the nitrile compound in the electrolyte and the mass proportion of the first additive.

[0111] The Example 6 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 4. Among them, in the Example 6 group, the Dv50 of the silicon-carbon material was changed.

[0112] Table 4

[0113]

[0114] It can be seen from Table 4 that the present invention can further reduce the viscosity of the electrolyte, reduce the interfacial impedance during the charge and discharge process of the battery, inhibit lithium plating at the negative electrode, and further improve the low-temperature cycle stability of the battery by adjusting the relationship between the Dv50 of the silicon-carbon material and the mass proportion of the first additive.

[0115] The Example 7 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 5. Among them, in the Example 7 group, the Dv50 of the positive electrode active material was changed.

[0116] Table 5

[0117]

[0118]

[0119] It can be seen from Table 5 that the present invention can improve the high and low temperature capacity retention rate of the battery and improve the cycle performance of the battery by adjusting the Dv50 of the positive electrode active material.

[0120] Example 8 was carried out in accordance with Example 1-1, and the main differences are shown in Table 6. In particular, Example 8 further added a third additive (FEC) to the electrolyte on the basis of Example 1-1, and changed the mass proportion of the third additive in the electrolyte.

[0121] Table 6

[0122]

[0123] It can be seen from Table 6 that the present invention, by adding the third additive to the electrolyte and adjusting the mass ratio of the third additive, is conducive to forming a dense interface film, reducing side reactions, and improving the cycle life of the battery.

[0124] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a carbon-based material and a silicon-based material; the silicon-based material includes a silicon-carbon material; the silicon-carbon material includes a core and a carbon coating layer coated on the core, and the core includes a porous carbon substrate and a silicon material distributed in the pores of the porous carbon substrate; the open pore volume of the silicon-carbon material is recorded as V cm 3 / g; The electrolyte includes a first additive, wherein the first additive includes ethyl 2,2-difluoroacetate and / or its derivatives; based on the total mass of the electrolyte, the mass proportion of the first additive is denoted as A1%; The electrolyte includes a second additive, wherein the second additive includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and / or its derivatives; based on the total mass of the electrolyte, the mass proportion of the second additive is recorded as A2%; A1 and A2 satisfy: 5≤A1+A2≤30; V satisfies: 0.0001≤V≤0.

1.

2. The lithium ion secondary battery according to claim 1, characterized in that: A1 satisfies: 1≤A1≤20; preferably 5≤A1≤15; And / or, A2 satisfies: 1≤A2≤20; preferably 2≤A2≤10.

3. The lithium ion secondary battery according to claim 1, characterized in that: Preferably, in the negative electrode active material, the mass percentage of silicon is 5%-50%; Preferably, V satisfies: 0.01≤V≤0.

1.

4. The lithium-ion secondary battery according to claim 1, characterized in that: The electrolyte further comprises a nitrile compound; the mass proportion of the nitrile compound based on the total mass of the electrolyte is recorded as N%; A1 and N satisfy: 12≤A1+N≤25.

5. The lithium ion secondary battery according to claim 4, characterized in that: N satisfies: 2≤N≤10, preferably 3≤N≤8; And / or, the nitrile compound includes one or more of a mononitrile compound, a dinitrile compound, and a trinitrile compound.

6. The lithium ion secondary battery according to claim 4, characterized in that: The Dv50 of the silicon-carbon material is denoted as d1 μm, and d1 and A1 satisfy: 1≤A1 / d1≤3; Preferably, d1 satisfies: 6≤d1≤12.

7. The lithium ion secondary battery according to claim 4, characterized in that: The positive electrode sheet includes a positive electrode active material, the positive electrode active material includes a transition metal lithium oxide, and the molecular formula of the transition metal lithium oxide is Li x Co y M 1-y O2, wherein 0≤x≤1, 0≤y≤1, and M includes one or more of Ni, Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr; Preferably, the Dv50 of the positive electrode active material is denoted as d2 μm, and d2 satisfies: 10≤d2≤30.

8. The lithium ion secondary battery according to claim 1, characterized in that: The silicon-carbon material includes a carbon coating layer, and the thickness of the carbon coating layer is 10nm-500nm; Preferably, the first additive comprises ethyl 2,2-difluoroacetate; and / or the second additive comprises 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon and soft carbon; And / or, the electrolyte further includes a third additive, and the third additive includes one or more of vinylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, fluoroethylene carbonate, tetravinylsilane, tris(trimethylsilyl)borate, hexamethyldisilazane, fluorobenzene, and triphenyl phosphite.

10. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The electrolyte includes an organic solvent, and the organic solvent includes a carbonate solvent and / or a carboxylate solvent; And / or, the electrolyte includes a lithium salt, and the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium bis(fluorosulfonyl)imide, lithium 4,5-dicyano-2-trifluoromethylimidazole, lithium difluorophosphate and lithium difluorobis(oxalato)phosphate.

Citation Information

Patent Citations

  • Electrolyte for high-voltage soft package lithium ion battery suitable for high-rate charging and discharging

    CN110707361A

  • Electrolyte and battery comprising same

    CN116646597A

  • Electrolyte and battery comprising same

    CN116960459A

  • Porous silicon composite material, porous silicon carbon composite material comprising same, and negative electrode active material

    CN116963999A

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN117673322A